The association between children’s oral health and parents’ socioeconomic position in Northern Norway - Thomassen, Jeanett Kraukle; Larsen, Beate (UiT Norges arktiske universitet, 2019)
Background: Dental caries is the most common chronic disease in children. In Norway there are government sponsored programs that give all children (0-18 years) free public dental treatment. This program seems to reduce the social gap in oral health compared to countries where dental treatment is paid out-of-pocket. There are indications that not all children in Norway benefit equally good from this program. Aims: The first aim of this thesis was to assess caries experience expressed as DMFT/dmft index among children in Northern Norway (Tromsø, Storslett and Mosjøen). The second aim was to investigate the association between children´s oral health and their parents´ socioeconomic position (SEP). Materials and method: This was a cross sectional study, that included 140 children and their parents. The children in the study were between 5 and 12 years old. The sample was recruited at University Dental Clinic in Tromsø (82, 30%), public dental clinic in Storslett (19, 76%) and public dental clinic in Mosjøen (39, 83%). Data was collected using a structured questionnaire asking about the child's gender, age, living area, number of people in the household, how long the child has lived in Norway, who the child lives with, last dental visit and the reason for the visit, rating of the child’s oral health, frequency of tooth brushing, help with tooth brushing, use of dental cleaning products, chronic diseases, medication, intake of sugar, parents´ age/education/occupation, household income and residence. DMFT/dmft value was measured on a routinely dental examination by a dentist or a dental hygienist. Results: The total mean caries experience was higher among older children. It was lowest for children at 5 years old (0,1 (0,4)) compared to children at 6-, 7-, 8,- 9, 11- and 12 years old ((0,4 (1,0)), (0,3 (0,7)), (0,5 (1,0)), (0,5 (0,7)), (0,6 (1,2)), (1,1 (2,0)) and (1,0 (1,4)), respectively). This difference was not statistically significance. The odds for a child to have DMFT≥1 decrease by 0,8 with each 50000NOK higher ...